Desarrollo social y la conservación de la biodiversidad para garantizar el desarrollo sostenible de especies fundamentales en la Isla Jambelí - Nagua Díaz, Juriko Nathaly (My University, 2021)
This research work was developed on the Jambelí Island belonging to the Archipelago of the same name located in the Santa Rosa canton in the El Oro province in southern Ecuador, the main objective of the research is to determine the main anthropic activities through scientific research for the correct social development and conservation of biodiversity. The field visit to the study site established the main activities carried out by its community members to survive and generate sources of work in the place, thus determining that tourism, the collection of fauna species for sale are the most common activities among the inhabitants. Despite being a great natural space and of great importance for the environment, its conservation is in danger due to the shrimp farming activity in the place, which has triggered a number of problems for the community members, affecting their correct social development and causing unfortunate damages in the place. A sustainable social development through bioethics seeks to generate a change in people's awareness to respect life and take care of the environment, the purpose of this is to generate a positive impact, undoubtedly mainly benefiting the inhabitants since well-conserved resources create a bridge to a better future. The intention of this study is to establish the importance of social development and sustainable development promoted from bioethics for the conservation of the habitat of many species that are being lost and that are fundamental for the trophic chain and the economic sustenance of many families.
El presente trabajo investigativo desarrollado en la Isla Jambelí perteneciente al Archipiélago Jambelí ubicado en el cantón Santa Rosa en la provincia de El Oro en Ecuador, el principal objetivo de la investigación es determinar las principales actividades antrópicas mediante la investigación científica para el correcto desarrollo social y conservación de la biodiversidad. La visita de campo al sitio de estudio estableció las principales actividades que realizan sus comuneros para generar fuentes de trabajo en el lugar determinando así que el turismo, la recolección de especies faunísticas para la venta son las actividades comunes entre los habitantes. A pesar de ser un gran espacio natural y de suma importancia para el ambiente, su conservación está en peligro debido a la actividad camaronera en el lugar se a desencadenando un sinnúmero de problemas para los comuneros afectando su correcto desarrollo social y ocasionando perjuicios lamentables en el lugar. Un desarrollo social sostenible mediante la bioética busca generar un cambio en la conciencia de las personas a que se respete la vida y se cuide el ambiente el fin de esto es generar un impacto positivo beneficiando sin duda principalmente a los habitantes ya que los recursos bien conservados crean un puente a un mejor futuro. La intención del estudio es establecer la importancia del desarrollo social y el desarrollo sostenible fomentado desde la bioética para la conservación del hábitat de muchas especies que se están perdiendo y que son fundamentales para la cadena trófica y el sustento económico de muchas familias.
Keywords: CONSERVACION; BIODIVERSIDAD; BIOETICA; DESARROLLO SOSTENIBLE